PEMBERDAYAAN PENGURUS AISYIYAH DENGAN PENGUATAN MANAJEMEN BISNIS - Endang Dwi Wahyuni; Sri Wibawani (Universitas Muhammadiyah Malang, 2020)
Science and technology for the Community (IbM) is intended to provide reinforcement for the management of business management Aisyiyah Twig Source Sekar and Jetak Ngasri Dau District of Malang. Aisyiah as social organizations have considerable social activities, for example in the fields of education, social, and community. Of course, to carry out these activities require considerable funds. The funds obtained from dues spontaneity or the officers and members of the donors and sympathizers. How to fund the acquisition of its existence is not one hundred percent reliable. Therefore, the board Aisyiah should start thinking about alternative sources of other funds, namely by establishing profit-oriented business units. Board Aisyiyah already have a business stub meatballs and nuggets but less good product display and marketing only to the scope of its own (for the surrounding communities). Based on this fact, IbM this time wanted to give a strengthening of business management for the board Aisyiyah. Strengthening the management here is more emphasis on production management and marketing as well as the accounting for business results. Team dedication to provide training related to business development, including: Tips entrepreneurship, Efficient Production Management, Marketing Strategy Strategies, Planning and Financial Management Small Business. In addition, the team dedication also provide assistance in the form of equipment: 2 pieces of meat milling machine, 1 meat mixer, and 1 hand sealer. Assistance was also given the initial capital to start production. Results are expected in the form of meatballs and nuggets products more attractive. Besides Tim also makes packaging and label design for brochures and trial manufacture of products using the machine and add the product variants. Other activities that have been carried out, namely: creating ads, advertise on the radio and on social networking Facebook. Operating results showed a significant increase, from an average sales per week 100 packs of meatballs and nuggets to 500 packs per week.